51 years of the Arboricultural Journal; a commentary. Issue 1 (2nd January 2017) - Helliwell, Rodney
Abstract : This paper provides a brief overview of the Arboricultural Journal from its inception in 1965 until 2015, with comments on some of the main topics, and thoughts on the development of arboriculture over this time, together with the role of the journal, both now and in the future. There were 163 issues of the journal over this period, and it has not been possible to mention every single item or topic, so the comments which follow are inevitably selective, and there may be some bias towards the subjects that have been of greatest interest to the reviewer or which appear to be of particular importance.